Effects of the Informed Health Choices secondary school intervention on the ability of students in Rwanda to think critically about health choices: A cluster-randomized trial - Mugisha, Michael; Nyirazinyoye, Laetitia; Senyonga, Ronald; Semakula, Daniel; Oxman, Andrew D. (Journal of Evidence‐Based Medicine, 2023)
The aim of this trial was to evaluate the effects of the Informed Health Choices intervention on the ability of students in Rwandan to think critically and make Informed Health Choices. We conducted a two-arm cluster-randomized trial in 84 lower secondary schools from 10 districts representing five provinces of Rwanda. We used stratified randomization to allocate schools to the intervention or control. One class in each intervention school had ten 40-min lessons taught by a trained teacher in addition to the usual curriculum. Control schools followed the usual curriculum. The primary outcome was a passing score (≥ 9 out of 18 questions answered correctly) for students on the Critical Thinking about Health Test completed within 2 weeks after the intervention. We conducted an intention-to-treat analysis using generalized linear mixed models, accounting for the cluster design using random intercepts. Between February 25 and March 29, 2022, we recruited 3,212 participants. We assigned 1,572 students and 42 teachers to the intervention arm and 1,556 students and 42 teachers to the control arm. The proportion of students who passed the test in the intervention arm was 915/1,572 (58.2%) compared to 302/1,556 (19.4%) in the control arm, adjusted odds ratio 10.6 (95% CI: 6.3–17.8), p < 0.0001, adjusted difference 37.2% (95% CI: 29.5%–45.0%). The intervention is effective in helping students think critically about health choices. It was possible to improve students’ ability to think critically about health in the context of a competence-based curriculum in Rwanda, despite challenging postpandemic conditions.